Observation of a Be double-Lambda hypernucleus in the J-PARC E07 experiment. (22nd February 2019) - Ekawa, H; Agari, K; Ahn, J K; Akaishi, T; Akazawa, Y; Ashikaga, S; Bassalleck, B; Bleser, S; Endo, Y; Fujikawa, Y; Fujioka, N; Fujita, M; et al.
Abstract: A double-$Λ$ hypernucleus, ${}_{ΛΛ}Be$, was observed by the J-PARC E07 Collaboration in nuclear emulsions tagged by the ($K^{-}, K^{+}$ ) reaction. This event was interpreted as the production and decay of $ {}_{ΛΛ}^{\;10}Be$, ${}_{ΛΛ}^{\;11}Be$, or ${}_{ΛΛ}^{\;12}Be^{*}$ via $Ξ^{-}$ capture in ${}^{16}O$ . By assuming capture in the atomic 3D state, the binding energies of two $Λ$ hyperons ($B_{ΛΛ}$ ) of these double-$Λ$ hypernuclei are obtained to be $15.05 ± 0.11\, MeV$, $19.07 ± 0.11\, MeV$, and $13.68 ± 0.11\, MeV$, respectively. Based on the kinematic fitting, ${}_{ΛΛ}^{\;11}Be$ is the most likely explanation for the observed event.